The methods of prediction of vaporization enthalpy for acyclic oxygen containing compounds - E. L. Krasnykh (Тонкие химические технологии, 2015)
In this paper were analyzed the prognostic opportunity of some semi-empirical methods (additive, additive-correlation, QSPR-methods) used to calculate enthalpies of vaporization (298.2K) acyclic oxygen-containing compounds. Used literature data and our own experimental research by the author in the development of the concept of molecular connectivity based on the index approach is proposed QSPR-method for the calculation of enthalpies of vaporization (298.2K) with high accuracy for the esters and ethers, aldehydes, ketones, alcohols and carboxylic acids.